Total laparoscopic hysterectomy for anterior cervical myoma: Possible significance of presurgical assessment by magnetic resonance imaging - Yumi Ishidera; Megumi Furugori; Go Hirata; Reina Wakabayashi; Hiroyuki Shigeta; Hiroshi Yoshida (Wolters Kluwer Medknow Publications, 2021)
Hysterectomy for large uterine anterior cervical myoma is a challenging surgical procedure. We summarize our experience in the management of large uterine anterior cervical myoma. Three patients underwent hysterectomy for uterine anterior cervical myoma with similar sizes and different positions treated by laparoscopic surgery. Total laparoscopic hysterectomy (TLH) for cervical myoma is possible by performing ureterolysis and adopting retrograde hysterectomy. Because the position of myoma is important to determine the difficulty of TLH, we propose to measure the axis between the most caudal point of the myoma and external cervical os and pubococcygeal line as a possible useful method in objectively predicting the difficulty of TLH for large anterior cervical myoma.